Assessment of ultrasound for use in detecting lipoatrophy in HIV-infected patients taking combination antiretroviral therapy - Višković, Klaudija (Array, 2009)
The aim of this study was evaluation of ultrasound (US) as a tool for the assessment of lipoatrophy in a population of HIV-infected patients. We enrolled a convenience sample of 151 HIV-infected Caucasian participants (males, 79%) who were treated for at least 1 year with combination antiretroviral therapy (CART) in Zagreb, Croatia. US measurements of subcutaneous fat thickness were done over the malar, brachial, and crural region. We determined sensitivity and specificity of US as a diagnostic tool for lipoatrophy using receiver-operating curves and concordant patient and clinician assessment as our reference for the presence of lipoatrophy. HIV was acquired through heterosexual contact in 50% of participants and by sex between men in 42%. The mean current CD4 cell count was 503.1 cells/mm3 (standard deviation [SD] = 250.8). Seventy-seven (51%) participants were treated with stavudine and 91 (64%) with a protease inhibitor for at least 6 months. Nineteen (13%) participants had lipoatrophy in at least one anatomic site. Sensitivity of US ranged from 67%-71%, specificity from 65%-71%, positive and negative predictive values ranged from 11%-20% and 96-97%, respectively. US-diagnosed lipoatrophy was more frequently found in patients with a history of stavudine treatment and in females. Patients with lipoatrophy had a longer duration of CART than those without lipoatrophy. US is a useful tool in ruling out the presence of clinical lipoatrophy in patients on CART. Using this objective measure of subcutaneous fat may be useful in helping clinicians make decisions about changing therapy.